Estimation of the productive potential of the Santander goat based on morphometric measurements and body índices - Torres Ruda, Daniel Felipe (Spei Domus, 2025)
Introduction: The Santandereana goat, recognized as an indigenous zoogenetic resource of the Santander department, plays a fundamental role in the rural economy and food security of arid zones in the Chicamocha Canyon. This study aimed to evaluate the productive capacity of young males by analyzing morphometric variables and body composition indices throughout their growth. Methods: Twenty-seven males of the breed were used, distributed into three age groups (4, 8, and 12 months), and maintained under controlled management and feeding conditions. Ten morphometric variables were evaluated: weight (kg), height at the withers (cm), height at the croup (cm), thoracic circumference (cm), abdominal circumference (cm), body length (cm), hip width (cm), hip length (cm), testicular circumference (cm), and testicular diameter (cm), along with the following indices: Body Composition Index (BCI), Lateral Body Composition Index (LBCI), Compactness Index, Anamorphosis Index (ANI), Pelvic Index (PIE), Transverse Pelvic Index (TPI), Longitudinal Pelvic Index (LPI), and Relative Thoracic Depth Index (RTPI). Results: The studies showed a progressive increase in body weight and morphological dimensions with age, with statistically significant differences (p
Keywords: Chicamocha Canyon; Creole goat; growth; morphometrics; animal genetic resource